Assisted death for prisoners and forensic patients: complexity and controversy illustrated by four recent cases - Roland M. Jones; Alexander I. F. Simpson (BJPsych Bulletin)
Medical assistance in dying (MAiD) (which includes euthanasia and assisted suicide) is available in an increasing number of countries. In Belgium, The Netherlands and Switzerland (and was due to be implemented in Canada from 2024) eligibility includes mental suffering in the absence of any physical disorder. There are particular ethical and legal issues when considering MAiD for those involuntarily detained in prisons and hospitals. We describe four recent cases that illustrate these complexities, and highlight issues of equivalence of healthcare and self-determination against concerns about the criteria for determining eligibility of those with non-terminal conditions as well as the objections raised by victims and families and the demands for justice.